The responsiveness and relevance of the activity of the participation outcome measure in patients with traumatic brain injury in an acute neurological rehabilitation setting - Camp, Alison Louise (My University, 2015)
Acute neurological rehabilitation aims to reduce the burden of care of patients with TBI and increase their activity participation. Weekly feedback to funders of private rehabilitation facilities using appropriate outcome measures is required. This study compares the Functional Independence Measure™+Functional Assessment Measure (FIM™+FAM) with the Activity Participation Outcomes Measure (APOM) responsiveness to change in TBI patients in the acute neurological rehabilitation phase of recovery. A quantitative, prospective, longitudinal design was used. Patients were scored weekly on both outcome measures. No significant difference was found between the responsiveness of the two measures. Both measures showed change in activity participation (APOM) and reduction of burden of care (FIM™+FAM). The relevance of the APOM to the TBI population was good with a correlation above 0.8 with the total FIM™+FAM. The APOM benefitted occupational therapists and the patient by assisting with goal setting and quantifying changes that the FIM™+FAM did not capture adequately. It is recommended that the APOM be used in future at the study site.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy Johannesburg 2015